Mitochondrial quality surveillance as a therapeutic target in myocardial infarction. (16th December 2020) - Zhu, Hang; Toan, Sam; Mui, David; Zhou, Hao
Abstract: Myocardial infarction (MI) is a leading cause of morbidity and mortality worldwide. As mitochondrial dysfunction critically contributes to the pathogenesis of MI, intensive research is focused on the development of therapeutic strategies targeting mitochondrial homeostasis. Mitochondria possess a quality control system which maintains and restores their structure and function by regulating mitochondrial fission, fusion, biogenesis, degradation and death. In response to slight damage such as transient hypoxia or mild oxidative stress, mitochondrial metabolism shifts from oxidative phosphorylation to glycolysis, in order to reduce oxygen consumption and maintain ATP output. Mitochondrial dynamics are also activated to modify mitochondrial shape and structure, in order to meet cardiomyocyte energy requirements through augmenting or reducing mitochondrial mass. When damaged mitochondria cannot be repaired, poorly structured mitochondria will be degraded through mitophagy, a process which is often accompanied by mitochondrial biogenesis. Once the insult is severe enough to induce lethal damage in the mitochondria and the cell, mitochondrial death pathway activation is an inevitable consequence, and the cardiomyocyte apoptosis or necrosis program will be initiated to remove damaged cells. Mitochondrial quality surveillance is a hierarchical system preserving mitochondrial function and defending cardiomyocytes against stress. A failure of this system has been regarded as one of the potential pathologies underlying MI. In this review, we discuss the recent findings focusing on the role of mitochondrial quality surveillance in MI, and highlight the available therapeutic approaches targeting mitochondrial quality surveillance during MI.